Dose-dependent Association between Intermediate-acting Neuromuscular-blocking Agents and Postoperative Respiratory Complications. (June 2015) - McLean, Duncan J.; Diaz-Gil, Daniel; Farhan, Hassan N.; Ladha, Karim S.; Kurth, Tobias; Eikermann, Matthias
<x xml:space="preserve">Abstract</x> Background: Duration of action increases with repeated administration of neuromuscular-blocking agents, and intraoperative use of high doses of neuromuscular-blocking agent may affect respiratory safety. Methods: In a hospital-based registry study on 48, 499 patients who received intermediate-acting neuromuscular-blocking agents, the authors tested the primary hypothesis that neuromuscular-blocking agents are dose dependently associated with the risk of postoperative respiratory complications. In the secondary analysis, the authors evaluated the association between neostigmine dose given for reversal of neuromuscular-blocking agents and respiratory complications. Post hoc, the authors evaluated the effects of appropriate neostigmine reversal (neostigmine ⩽60 μg/kg after recovery of train-of-four count of 2) on respiratory complications. The authors controlled for patient-, anesthesia-, and surgical complexity–related risk factors. Results: High doses of neuromuscular-blocking agents were associated with an increased risk of postoperative respiratory complications (n = 644) compared with low doses (n = 205) (odds ratio [OR], 1.28; 95% CI, 1.04 to 1.57). Neostigmine was associated with a dose-dependent increase in the risk of postoperative respiratory complications (OR, 1.51; 95% CI, 1.25 to 1.83). Post hoc analysis revealed that appropriate neostigmine reversal eliminated the dose-dependent association between neuromuscular-blocking agents and respiratory complications (for neuromuscular-blocking agent effects with appropriate reversal: OR, 0.98; 95% CI, 0.63 to 1.52). Conclusions: The use of neuromuscular-blocking agents was dose dependently associated with increased risk of postoperative respiratory complications. Neostigmine reversal was also associated with a dose-dependent increase in the risk of respiratory complications. However, the exploratory data analysis suggests that the proper use of neostigmine guided by neuromuscular transmission monitoring results can help eliminate postoperative respiratory complications associated with the use of neuromuscular-blocking agents.